THE PLAGIOGRANITE - FeTi-OXIDE GABBRO ASSOCIATION OF VERNE (MONVISO METAMORPHIC OPHIOLITE, WESTERN ALPS) - Castelli, Daniele; Lombardo, Bruno (Ofioliti, 2007)
The Verné plagiogranite-FeTi-oxide gabbro association is exposed in the southern Basal Serpentinite Unit of the Monviso meta-ophiolite and consists of a tabular body (about 400 x 250 m wide and 70 m thick) of jadeite - quartz - bearing massive metaplagiogranite in primary contact with omphacite - garnet - rutile ± glaucophane eclogite (recrystallized FeTi-oxide gabbro). Albite - quartz - bearing leucocratic layers within the metaplagiogranite body are interpreted as late-magmatic dikes. Despite Alpine re-crystallization under eclogite-facies conditions, both the FeTi-oxide gabbros and the plagiogranites retain most of their primary geochemical features. Composition of the Verné FeTi-oxide gabbros (average Mg# = 31.8) is very similar to those of FeTi-oxide metagabbros from other units of the Monviso meta-ophiolite. Their REE chondrite-normalized patterns are characterized by the typical MORB depletion in LREE; two samples are between 10 and 13 times chondrite and display rather flat patterns; one sample (also having the highest contents in Ce and Zr) is about 100 times chondrite and displays a negative Eu anomaly. The plagiogranites (64.20 < SiO2 < 65.90 wt%, 7.23 < Na2O < 8.28, average Mg# = 19.1) are leucocratic, Fe-rich quartz diorites; the plagiogranite dikes (SiO2 = 70.85 wt%, FeOtot = 3.37 wt% and average Mg# = 17.3) are more differentiated trondhjemite varieties. All plagiogranites are Zr-enriched rocks lying along a typical MORB differentiation trend. Their REE chondrite-normalized patterns are also typical of MORB, ranging between 20 and 500 times chondrite. All samples display a negative Eu anomaly, ranging from weak to strong. The Verné association represents late stages of the plutonic activity within ultramafic oceanic crust and its occurrence can be modelled by fractional crystallization of an evolved tholeiitic magma, possibly of oceanic andesite composition. After fractional crystallization of the FeTi-oxide gabbros, the remaining liquid has a composition similar to those of the plagiogranites, suggesting that these formed essentially from direct crystallization of such a residual liquid. The trondhjemite dikes, being the most differentiated liquids, were probably emplaced through deformation-controlled, late-stage melt migration in the nearsolidified crystal mush of the plagiogranite.